2014
DOI: 10.1111/1471-0307.12148
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amine content in Chilean Gauda cheese: physico‐chemical and microbiological factors that may influence this content

Abstract: The presence of four biogenic amines in Chilean Gauda cheese was studied, and the effect of certain factors may influence the production of those amines. Histamine, tyramine, putrescine and cadaverine were quantified with high-performance liquid chromatography (HPLC), in cheeses from the three major Chilean cheese manufacturers. Multiple regression analysis revealed that water activity, free amino acid content and the Enterobacteriaceae count all favoured production of biogenic amines. The total amount of biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In spite of good results with FLD, both studies showed that an UV detector is more appropriate for the determination of histamine. Several studies also reported LOD lower than 1 mg/kg for different BA in cheese using this system of detection (Brito et al, 2014;Sawilska-Rautenstrauch et al, 2010), thus achieving better sensitivity than most studies conducted with UV-Vis detection.…”
Section: Fluorescence Detectionmentioning
confidence: 88%
See 1 more Smart Citation
“…In spite of good results with FLD, both studies showed that an UV detector is more appropriate for the determination of histamine. Several studies also reported LOD lower than 1 mg/kg for different BA in cheese using this system of detection (Brito et al, 2014;Sawilska-Rautenstrauch et al, 2010), thus achieving better sensitivity than most studies conducted with UV-Vis detection.…”
Section: Fluorescence Detectionmentioning
confidence: 88%
“…Furthermore, according to number of amino groups, they can be classified as monoamines, diamines, or polyamines (Ladero et al, 2017;Spano et al, 2010). An extensive variety of BA is usually present in plants, animals (Farooqui, 2013), and foods (Naila et al, 2010), but the most important BA in certain foods and beverages are histamine, tyramine, putrescine, cadaverine, tryptamine, spermidine, spermine, and phenylethylamine, which are produced by decarboxylation of their respective amino acids (Brito et al, 2014;del Rio et al, 2017;Palermo et al, 2013;Restuccia et al, 2011;Spano et al, 2010), as can be seen in Table 1. BA act as precursors for the synthesis of hormones, alkaloids, nucleic acids, and proteins; some of them, such as histamine and tyramine, play an important role as neurotransmitters (del Rio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The content of biogenic amines such as histamine, tyramine, ethylamine, or phenyletilamine in foods should be controlled since, in susceptible consumers, their presence can cause health problems such as headaches, nausea, and vomiting, allergies, an increase of arterial blood pressure. Moreover, some biogenic amines like cadaverine and putrescine are responsible for the undesirable flavor in some foods (Brito, Cid, Muñoz, Báez, & Horzella, ). The degree of toxicity depends on the amine type and concentration and may be increased by the presence of other amines; for example, cadaverine and putrescine facilitate intestinal absorption of histamine due to blockage of monoamine oxidase enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…The most common amines found in ripened cheeses are histamine, tyramine, putrescine, and cadaverine and they are produced mainly by LAB (Brito et al, ), but phenylethylamine, ethylamine, and tryptamine can be present, too (Fernández, Linares, Río, Ladero, & Álvarez, ; Poveda, Chicón, & Cabezas, ; Schirone, Tofalo, Visciano, Corsetti, & Suzzi, ). There are many studies concerning amine presence in cheeses, which depends on the origin and treatment of the milk and on the manufacturing process, in which the hygienic conditions and the length of the ripening period play a significant role (Fernández et al, ).…”
Section: Introductionmentioning
confidence: 99%